Temperature-driven mechanisms of hydrogen embrittlement and electrochemical corrosion in Ni-based superalloy 600 - Jiaqing Li; Xi Yu; Zhiye Zheng; Kai Lu; Lin Teng; Yu Ding; Zhuwu Zhang; Hui Wang; Che Zhang; Lilong Jiang (Journal of Materials Research and Technology)
The temperature-dependent mechanisms for hydrogen-induced embrittlement and electrochemical corrosion in Ni-based superalloy 600 have been unravelled by means of tensile tests and potentiodynamic polarization tests under electrochemical environment. Increasing temperature accelerates electrochemical corrosion behaviour and induces the transition into intergranular corrosion, whereas there exists critical temperature THE, max, in which hydrogen-induced ductility loss reaches its peak. Detailed electron microscopy and thermal desorption spectroscopy analysis demystify that intergranular brittle fracture at THE, max is predominantly driven by hydrogen-dislocation-grain boundary interactions, compounded by high diffusible hydrogen content. These findings offer new insights into the critical role of temperature in modulating hydrogen embrittlement and corrosion, contributing to the design of materials in hydrogen environment.